Atmospheric Sounding by TAMDAR over Keflavík Airport, Iceland - Comparison with Traditional Atmospheric Sounding Methods - Arnór Tumi Jóhannsson 1992- (2016)
Tropospheric measurements by radiosonde and Tropospheric Airborne Meteorological Data Reporting (TAMDAR) over Keflavík airport, Iceland, were compared in an effort to assess the potential benefit of implementing TAMDAR data in the observations and forecasting system of the Icelandic Meteorological Office (IMO). Despite a relatively small dataset and considerable spatial variability in the data, it was concluded that TAMDAR performs well in measuring temperature. Temperature measurements of radiosonde and TAMDAR were generally in good agreement. Furthermore, the results suggest that TAMDAR does well at assessing wind direction. TAMDAR detects variations in relative humidity and is generally in accordance with relative humidity forecasts. The quality of TAMDAR wind speed measurements is difficult to determine, however discrepancies between wind speed measured by radiosonde and TAMDAR can usually be explained to some degree by forecast or observed spatial variability in wind. It is concluded that implementing TAMDAR data into the observations and forecasting system of the IMO would nicely supplement traditional atmospheric soundings to increase the coverage and frequency of atmospheric measurements in Icelandic airspace. Háloftamælingar með veðurkanna (e. radiosonde) voru bornar saman við háloftamælingar framkvæmdar af TAMDAR yfir Keflavíkurflugvelli. Tilgangur verkefnisins var að meta mögulegan ávinning þess að innleiða TAMDAR-gögn í athugunar- og spákerfi Veðurstofu Íslands. Þrátt fyrir fremur lítið gagnasafn og mikinn breytileika í rúmi var ályktað sem svo, að hitamælingar TAMDAR væru áreiðanlegar og í góðu samræmi við hitamælingar veðurkanna. Niðurstöður verkefnisins benda til þess að vindáttarmælingar TAMDAR séu almennt góðar. TAMDAR nemur breytingar í loftraka og eru loftrakamælingar í samræmi við spár að allnokkru leyti. Gæði vindhraðamælinga TAMDAR eru torræð, en yfirleitt má skýra ósamræmi milli vindhraðamælinga veðurkanna og TAMDAR með þeim breytileika sem fram kemur í spám eða athugunum. Innleiðing ...